Sharing Sessions and Educational Videos Increase Nurses Knowledge about Effective Communication in the 2019 Coronavirus Disease Pandemic - Yanti, Emy Darma; Krisnawati, Komang Menik Sri (Journal of Language and Health, 2021)
The 2019 Coronavirus Disease pandemic caused nurses to communicate more indirectly to patients being treated. This requires a strategy so that nurses can still apply communication effectively during the 2019 Coronavirus Disease pandemic. The purpose of this study was to analyze the effect of sharing sessions and providing educational videos on nurses' knowledge about The 2019 Coronavirus Disease pandemic caused nurses to communicate more indirectly to patients being treated. This requires a strategy so that nurses can still apply communication effectively. The purpose of this study was to analyze the effect of sharing sessions and providing educational videos on nurses' knowledge about effective communication during the 2019 Coronavirus Disease pandemic at Udayana University Hospital. This research is a quantitative study with a pre-experimental one group pretest-posttest design method which was conducted on 21 respondents with a total sampling. Sharing sessions are conducted in one day for two hours and educational videos is carried out for seven days with a video duration of 15 minutes. Data collection used a questionnaire which consisted of 10 questions. The mean value of the pre-test was 5.57 and the mean value of the post-test was 8.68. The Wilcoxon test results obtained a p value of 0.000, meaning that there is an effect of sharing sessions and providing educational videos on nurses' knowledge about effective communication during the 2019 Coronavirus Disease pandemic. The sharing session program and the provision of educational videos can become routine programs implemented as an effective effort to increase knowledge nurses on effective communication. communication during the 2019 Coronavirus Disease pandemic in the Isolation Room Udayana University Hospital. This research is a quantitative study with a pre-experimental one group pretest-posttest design method which was conducted on 21 respondents with a total sampling. Sharing sessions are conducted in one day for two hours and the provision of educational videos is carried out for seven days with a video duration of 15 minutes. Data collection used a knowledge questionnaire about effective communication of nurses during the 2019 Coronavirus Disease pandemic which consisted of 10 questions. The mean value of the pre-test was 5.57 and the mean value of the post-test was 8.68. The Wilcoxon test results obtained a p value of 0.000, meaning that there is an effect of sharing sessions and providing educational videos on nurses' knowledge about effective communication during the 2019 Coronavirus Disease pandemic. The sharing session program and the provision of educational videos can become routine programs implemented as an effective effort to increase knowledge nurses on effective communication.